Pengaruh Kecerdasan Emosional dan Kemandirian Belajar Siswa terhadap Hasil Belajar PAI - M. Bagus Ridwan; Siti Halimah; Yusnaili Budianti (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Many students tend to be more interested in seeing their classmates' work achievements than trying and considering doing the assignments given by the teacher. This condition causes delays in students' thinking processes and efforts, which prioritize the influence of others rather than trusting their personal abilities. This research aims to explore the impact of emotional intelligence and learning independence on student learning outcomes at Al-Ma'sum Stabat Vocational School. The research method uses a second item relationship test, including Ordinarity, Homogeneity and Linearity Tests. The results of the individual t test show that there is no correlation between X1 (emotional intelligence) and Y (PAI learning outcomes) in the learning of class X TBSM students at Al-Ma'sum Stabat Vocational School. However, the results of the F test indicate that there is a joint influence between X1 (the ability to appreciate people deeply) and X2 (student learning independence) on Y (PAI learning outcomes) in this class.